1981
DOI: 10.1172/jci110035
|View full text |Cite
|
Sign up to set email alerts
|

Immune Complexes in Serum and in Cerebrospinal Fluid in African Trypanosomiasis

Abstract: A B S T R A C T The possible occurrence of immune complexes (IC) in serum and in cerebrospinal fluid (CSF) has been studied in 36 patients with African trypanosomiasis (Trypanosoma brucei gambiense). In serum, very high levels of IC were detectable by the '25I-Clq-binding and by the conglutinin-binding assays with positive results in 94 and 87%, respectively, of untreated patients. Circulating IC were found in both early and late stages of the disease, without significant quantitative differences; their size w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(26 citation statements)
references
References 11 publications
(10 reference statements)
0
25
1
Order By: Relevance
“…In the literature available to the present authors no case has been reported. Hypoplasia of the pulmonary trunk without a ventricular septal defect is well known in man (2,5,8) as well as in animals (1, 4,6,7). This is a report of such an anomaly in a goat lamb.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the literature available to the present authors no case has been reported. Hypoplasia of the pulmonary trunk without a ventricular septal defect is well known in man (2,5,8) as well as in animals (1, 4,6,7). This is a report of such an anomaly in a goat lamb.…”
Section: Introductionmentioning
confidence: 76%
“…A very severe trypanosoma infection, like the case here reported, can suppress the cellular immune response. However, with the disappearance of the infection the reticulo-endothelial system should again be able to react (6). Renewed exposure with the antigen for which sensitization has taken place, can cause a hypersensitivity reaction (12).…”
Section: Historymentioning
confidence: 99%
“…[29][30][31] IgM and interleukin-10 (IL-10) in CSF are typical components of the neuroinflammatory response in patients with the brain stage of Trypanosoma brucei gambiense infection. 32 The intrathecal synthesis patterns in Cuban adults do not vary compared with children, and it is a typical immune response that supports the diagnosis. IgG is always present in such patterns.…”
Section: Resultsmentioning
confidence: 92%
“…First evidence for the occurrence of this type of immune complex came from studies on human African trypanosomiasis [16]. In these patients, a close correlation was found between the level of circulating immune complexes and the level of rheumatoid factor-like antibodies, suggesting an involvement of these antibodies in the formation of immune complexes.…”
Section: Of Lpsmentioning
confidence: 98%